2011
DOI: 10.4236/me.2011.23029
|View full text |Cite
|
Sign up to set email alerts
|

Do Spatial Price Indices Reshuffle the Italian Income Distribution?

Abstract: This paper examines how spatial price differentials affect income distribution in Italy. Established results concerning disparities between the Northern and Southern regions of Italy hold up when adjusting incomes for the regional purchasing power. Poverty is still concentrated in the Southern part of the country. Furthermore, the cost-of-living indices that have the highest impact on the Italian income distribution are those accounting for regional differential in housing prices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…As expected, the variability within regions remained stable due to the level (regional capital city) for which local PPPs were available. Similar results were obtained byPittau et al (2011).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…As expected, the variability within regions remained stable due to the level (regional capital city) for which local PPPs were available. Similar results were obtained byPittau et al (2011).…”
supporting
confidence: 90%
“…While considerable resources have been spent by statistical agencies for calculating PPP rates between countries, the issue of intra-national PPPs has received much less attention. Nevertheless, detailed price data required for the computation of local PPPs are not usually available at subnational level (Pittau et al 2011).…”
Section: Computation Of Local Ppps For Italymentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors favour the adjustment of ARoP rates by excluding housing costs (rent and mortgage interest) from disposable income (e.g. Aaberg et al., 2008; Pittau et al., 2011). The rationale for this change is that housing costs are the most significant component of regional differences in the cost of living within countries, and that excluding them is a way to ‘level the playing field’ between the regions.…”
Section: The Arop Rate As An Indicatormentioning
confidence: 99%
“…Both phenomena could affect our measure of PED by showing more people with low income than the actual value. However, a study found that price differentials do not compensate for the differences in incomes, although they reduced the north-south gradient [ 40 ]. Regardless of all, the threshold we used of € 10,000 per year is very low, and gross incomes lower than this threshold are hardly considered adequate for living in any part of Italy.…”
Section: Discussionmentioning
confidence: 99%